2021
DOI: 10.1001/jamainternmed.2021.0204
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Equipment to Help With Bathing and Toileting Among Older US Adults

Abstract: Home modification through seemingly mundane equipment, such as grab bars and shower seats, mitigates injury, dependence, and reduced quality of life in older adults coping with increasing disability. However, whether these interventions are underused in the US is unclear.OBJECTIVE To estimate how many older adults who need equipment to help with bathing and toileting do not have it, describe factors associated with not having equipment, and describe how many who did not initially have equipment acquired equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…We propose incorporating simple geriatric assessments into the routine care of people with COPD. Such assessments are likely to uncover unmet need for assistive devices (e.g., walkers and canes, durable medical equipment (e.g., shower chairs), strength training or consideration for additional care (e.g., disability parking placards, in-home caregiving) ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose incorporating simple geriatric assessments into the routine care of people with COPD. Such assessments are likely to uncover unmet need for assistive devices (e.g., walkers and canes, durable medical equipment (e.g., shower chairs), strength training or consideration for additional care (e.g., disability parking placards, in-home caregiving) ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, social workers can offer support, counsel, and referrals to social engagement and caregiving resources, physical therapists can help address sarcopenia and frailty, behavioral health specialists can provide counseling and treatment for depressive symptoms, and medical assistants, nursing staff, respiratory therapists and pharmacists can ensure medication lists are up to date and patients are trained in correct inhaler device use. Well-informed providers and clinics can and should assess for unmet medical equipment needs to reduce the mismatch between an individual's environment and their physical capabilities (e.g., shower chairs, raised toilet seats, grab bars, canes, walkers, and disability parking placards) ( 50 ). Finally, pulmonary specialty training should include geriatrics education, and providers should enter independent practice armed with specialization in age-friendly COPD care ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of evidence-based programs to increase environmental safety, functional independence, and occupational engagement within the homes of older adults is critical ( Stark et al, 2017 ; Stav et al, 2012 ; Szanton et al, 2011 ). Within the United States, an estimated 12 million people aged ≥65 years who are living in their own homes need equipment to aid with the activities of daily living (ADLs); however, roughly five million seniors lack those items ( Lam et al, 2021 ); and 75% have reported at least one functional difficulty ( National Center for Health Statistics, 2018 ). Therefore, it is necessary to understand how to support the occupational, functional, and quality of life needs of community-dwelling older adults, utilizing effective and evidence-based intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Echoing this, grab bars are often considered to be a component of the bathroom environment that is appropriate only for older adults or people with disabilities, which is reflected in three common reasons for not having a grab bar: perceived stigma associated with assistive devices ( 14 , 15 ), perception that a grab bar is unnecessary ( 16 ), and a desire for normalcy and avoidance of permanent changes ( 17 ). As a result, grab bars are frequently absent from bathing environments, even in the homes of individuals who have been identified as having a specific need for a grab bar ( 18 , 19 ). Factors such as younger age, and not having a distinct event such as hospitalization or knee or hip injury are risk factors for unmet need for bathing assistive devices ( 19 ), indicating that mismatched perceptions of utility, ability, ageism and ableism contribute to the absence of necessary grab bars.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, grab bars are frequently absent from bathing environments, even in the homes of individuals who have been identified as having a specific need for a grab bar ( 18 , 19 ). Factors such as younger age, and not having a distinct event such as hospitalization or knee or hip injury are risk factors for unmet need for bathing assistive devices ( 19 ), indicating that mismatched perceptions of utility, ability, ageism and ableism contribute to the absence of necessary grab bars. As a public health intervention to address the prevalence of preventable bathing-related falls, the Universal Design approach of including of grab bars in all bathing environments may circumvent these concerns by shifting perceptions of grab bars to that of a typical bathroom element, rather than a stigmatized assistive device.…”
Section: Introductionmentioning
confidence: 99%